Environmental dermatology: skin manifestations of injuries caused by invertebrate aquatic animals - Vidal Haddad Junior (Sociedade Brasileira de Dermatologia, 2013)
Contact between humans and coastal areas has increased in recent decades, which has led to an increase in injuries from aquatic animals. The majority of these present dermatological manifestations, and some of them show typical lesions. The highest percentages of injuries that occur in marine environments are associated with invertebrates such as sea urchins, jellyfish and Portuguese men-of-war (echinoderms and cnidarians). In this review, we discuss the clinical, therapeutic and preventive aspects of injuries caused by marine and freshwater invertebrates, focusing on first aid measures and diagnosis for dermatologists and professionals in coastal areas.